Utilização de planejamento doehlert para avaliação da estabilidade de antibiótico para uso veterinário - Bonamichi, Luiz Americo Verginio (Universidade Federal de São Carlos, 2023)
USE OF DOEHLERT PLANNING FOR EVALUATING THE STABILITY OF VETERINARY ANTIBIOTICS. Before a veterinary pharmaceutical product reaches its final customer for commercialization, several regulated production chain must be performed to guarantee its quality. These steps encompass manufacturing process, such as pharmaceutical input, packaging, distribution, and commercialization. Before being used in the manufacturing stage of veterinary products, pharmaceutical inputs are evaluated through the company's quality parameters, with the goal of ensuring that they are suitable for use in the formulation without compromising the quality of the final product. Nowadays, companies seek a deeper understanding of the stability of active pharmaceutical ingredients (APIs), which are the excipients that provide the medicinal properties to pharmaceutical products. In this initial stage of product development, the concept of Quality by Design (QbD) is applied, to understand the critical points that affect the stability of these inputs avoiding issues in the production process. Thus, to study the stability of the antibiotic used in the company, the analytical technique of high-performance liquid chromatography (HPLC) was employed. With chromatography, it is possible to separate and quantify the substances present in the raw material. The analytical method used in this project was developed and validated by the company itself. With the assistance of Chemometrics, an experimental design was carried out to explore the understanding of antibiotic stability in relation to three variables: time, temperature, and oxidation by the atmospheric air (dead volume). The data was processed using the LCSolution and Octave programs. The studied antibiotic was stable in the experimental model, and the variables investigated presented negligible effects. In addition, the design of experiments (DoE) was efficient and crucial in reaching this conclusion.
Use of doehlert planning for evaluating the stability of veterinary antibiotics
Keywords: Planejamento; Doehlert; Estabilidade; Veterinário; Stability; Antibiótico; Antibiotics; Veterinary; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA